Entre o risco e o ponto : o intangível consumido - Andrade, Elza Guimarães (2012)
This dissertation presents an anthropological research about ´´Renda Irlandesa``(Irish Lace) Sergipe´s handicraft that had its modi faciendi registered as National Intangible Cultural Heritage, in the Book of Knowledge, in November 2008 - in an approach that introduces new directions for addressing production, marketing and use, resulting from its interaction with the fashion market. The research focuses on a new approach that tends to treat consumption as a matter of culture, analyzing the emergence of new attitudes assumed by artisans in the ´´know-how Renda Irlandesa`` amid the demands of the fashion market linked to women´s clothing, which provide potential use of formulating handmade garments. It highlights the processes of the cultural heritage exerted by the female artisans in their know-how and shape the cultural heritage of handicrafts, emphasizing its role as a complementary source of income for the protagonists of the practice. Finally, we discuss the new mechanisms of representation made by social workers from the symbolic consumption of cultural heritage.